Environmental, social and governance (ESG) performance and earnings management: the role of gender diversity - Vincentia Anindha Primacintya; Indra Wijaya Kusuma (AJAR (Asian Journal of Accounting Research))
Purpose – This study investigates the impact of ESG performance on earnings management practices in Indonesia and also examines whether gender diversity on the board of commissioners moderates this relationship. Design/methodology/approach – The sample of this study consisted of nonfinancial companies listed on the Indonesia Stock Exchange from 2014 to 2022. ESG performance is proxied by the ESG score; earnings management is calculated by the Jones modified model. Gender diversity is represented by the proportion of female board commissioners. This research employs a balanced panel; after conducting model tests, the common effect model is used to test the first hypothesis, and the fixed effect model is applied to test the second hypothesis. Findings – This study provides empirical evidence that higher ESG performance in a company is associated with lower earnings management. Companies with a diverse gender composition on their board of commissioners demonstrate a stronger negative relationship between ESG performance and earnings management. Research limitations/implications – Empirical evidence on company ESG performance is important because Indonesia, as a G20 member, is striving to maximize the implementation of the SDGs. This study provides empirical evidence on the significance of Goal 5 of the SDGs, which pertains to gender equality in Indonesia. Originality/value – This study complements previous research on ESG in Indonesia by providing empirical evidence on the impact of strong ESG performance among companies. Referring to Indonesia’s two-tier board system and Goal 5 of the SDGs, which focuses on gender equality, this study examines the value of gender diversity on the board of commissioners.